Cognitive alterations in juvenile Parkinson´s disease caused by the C212Y mutation in the Parkin gene (2010)
In Antioquia, Colombia, four families have been reported with juvenile Parkinson´s disease and carrying the C212Y mutation in the Parkin gene. For this study we selected a group of ten homozygous carriers of Parkin mutation C212Y with diagnosis of PD, and ten healthy relatives as controls. The neuropsychological evaluation revealed statistically significant differences between the two groups (p < 0.05) in Minimental State Examination and in tests evaluating working memory and attention in which prolonged execution times and marked slowing down of information processing were observed. We suggest that the observed alterations could be considered as neuropsychological features of patients with the C212Y mutation in the Parkin gene, the phenotypic expression of which seems to be associated in this population with slow evolution, mild cognitive impairment and functional involvement.